Field study 2 : experiencing the teaching-learning process - Corpuz, Brenda B. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2010)
FS 2 Workbook aligns the learner's experiences with the National Competency-Based Teachers Standards (NCBTS). THE learning experiences embedded in every lesson were intended to create meaningful and rewarding encounters to ensure that the students will feel the joy of teaching and learning. FS2 is focused on Principles of Learning experiences, Lessons Objectives as My Guiding Star, Organizing Content for Meaningful Learning, Guiding Principles on the Selection, and Use of Teaching Strategies, Teaching Approaches and Methods, Lesson development, Effective Questioning and Reacting techniques.
Foreword iii -- Preface iv -- Table of Contents vi -- Letter to the Field Student vii -- Letter to the Field Study Teacher viii -- Orientation Notes for Field Study and This Workbook ix -- Approach to Field Study 2 x -- Matrix of Field Study 2 -- Suggested Guidelines for Field Study Students xii -- Episode 1 - Principles of Learning 2 -- Episode 2 - Lesson Objectives as My Guiding Star 11 -- Episode 3 - Organizing Content for Meaningful Learning 18 -- Episode 4 - Guiding Principles in the Selection and Use of Teaching Strategies 26 -- Episode 5 - On Teaching Approaches and Methods 33 -- Episode 6 - On Development 42 -- Episode 7 - Effective Questioning and Reacting Techniques 49 -- Prescribed Certificate of Completion for Experimental Learning Courses 58.
Keywords: EDUCATION -- PHILIPPINES